Upaya Meningkatkan Kreativitas Anak Melalui Metode Menggambar Bebas Pada Kelompok BI di Taman Kanak – Kanak Tunas Harapan Seberida - Chindra Chindra; Elvi Wahyuni; Erniati Erniati (Jurnal Pendidikan Tuntas, 2023)
Children's low interest in creating their own work and not being able to complete their play activities well is the reason why this research was conducted. The researcher provided a solution in the form of increasing children's creativity through the free drawing method in the BI group at Tunas Harapan Seberida Kindergarten. The research applied is of the type collaborative Class Action Research. In this case, researchers collaborate with colleagues to find solutions to problems that occur. Researchers and collaborators work together to prepare learning methods and tools and discuss evaluating learning. The research stages are the planning, implementation, observation and reflection stages. The data collection technique used in this research is observation. Observation is the process of collecting data in research by observing every event that takes place and recording the things studied using observation tools. Research instruments are tools used to collect research data. The observation instruments used in this research were checklist instruments and work results. increase in the percentage of learning activity assessment results through drawing. Where in the pre-cycle the creative ability of children was found to be 7%, while in the first cycle 33% of children were creative and in the second cycle the optimal expected ability was 100%. Interesting media and learning strategies can stimulate children's interest in drawing. Apart from that, the teacher's role is very important as a model, as a motivator, and as a facilitator for children. Keywords: creativity, Free Drawing Method, Classroom Action Research